Предмет: Алгебра, автор: Юляка2000

(m^1/4-m^1/3)^2+2m^7/12 Решите!!ДАЮ 50 баллов!!!

Ответы

Автор ответа: GREENDEY
0
(m^{ frac{1}{4}} -m^{ frac{1}{3}})^2+2m^{ frac{7}{12}}=(m^{ frac{1}{4}})^2-2m^{ frac{1}{4}} m^{ frac{1}{3}}+ (m^{ frac{1}{3}})^2+2m^{ frac{7}{12}}= \ 
=m^{ frac{1}{2}}-2m^{ frac{1}{4}+frac{1}{3}} +m^{ frac{2}{3}}+2m^{ frac{7}{12}}=m^{ frac{1}{2}}-2m^{ frac{7}{12}} +m^{ frac{2}{3}}+2m^{ frac{7}{12}}= \ 
=m^{ frac{1}{2}}+m^{ frac{2}{3}} \
Похожие вопросы
Предмет: Алгебра, автор: asorokin46